If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(4x + 4) = 8x + -34 Reorder the terms: 9x + -1(4 + 4x) = 8x + -34 9x + (4 * -1 + 4x * -1) = 8x + -34 9x + (-4 + -4x) = 8x + -34 Reorder the terms: -4 + 9x + -4x = 8x + -34 Combine like terms: 9x + -4x = 5x -4 + 5x = 8x + -34 Reorder the terms: -4 + 5x = -34 + 8x Solving -4 + 5x = -34 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + 5x + -8x = -34 + 8x + -8x Combine like terms: 5x + -8x = -3x -4 + -3x = -34 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + -3x = -34 + 0 -4 + -3x = -34 Add '4' to each side of the equation. -4 + 4 + -3x = -34 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = -34 + 4 -3x = -34 + 4 Combine like terms: -34 + 4 = -30 -3x = -30 Divide each side by '-3'. x = 10 Simplifying x = 10
| 9x-18y=72 | | -5m=4m-9 | | 6(x+4)-9=19-6x-4+12x | | -[7x-(2x+6)]=-3-[3(3x-4)-2x] | | -5.4(2t+4)-2.3(4t-6)= | | 6x+9=35 | | 4-x^2+2x+x-2=0 | | 5(a-8)+8=2(a-7) | | 2x-5+3=-34 | | 7[3-(4+2x)]-4x=-9+2(1-9x) | | 8+4+x=5+7 | | -9=x/5 | | 0.80x+0.05(8-x)=0.10(34) | | -4x=-42+2x | | 3x=4x+28 | | 2/(x-1)=(x+2)/2 | | -[10z-(13z+6)]=6+(2z+0) | | 2/(x-1)-(x+2)/2=0 | | 4/5/3=16/10/6 | | [4+(-4)]y= | | 33=9+x | | 7x+-17= | | 1x+3=1/2 | | -8(x+1)-x-8=-9(x+5)+29 | | X^2-14x-33=0 | | -10=-4p+6 | | 3v=2v+4 | | (s+20)(s-24)=0 | | 15(v+3)-3v=(4v+1)-7 | | 49+14c+c= | | 3x-2=4(x-2)-5 | | 9+2x=3x |